Teori Himpunan: Sebuah Studi Tentang Teori Ukuran Lebesgue Dan Fungsi Cantor - Dika Tamara Dewi; Melati Rianingsi; Santi Yani Narwawan; Halima Rumaday; Prihaten Maskhuliah (Institut Nalanda, 2024)
Set theory is a mathematical science that studies the theory associated with abstract collections of objects. These collections can be defined as distinct objects and can already be proven clearly and can be seen as a unified whole. Set theory is related to Lebesgue Measure Theory because, this measure maps Algebra to . Henry Lebesgue (1902) compiled a measure theory known as the Lebesgue measure. By using this measure theory, there can be a correlation with the cantor set. The reason is that Lebesgue measure theory is one of the set forms that has zero Lebesgue measure where there is a cantor function in it which is an uncountable set. The purpose of this article is to discuss the relationship between Lebesgue measure theory and cantor function on a set.